The diligencia (stagecoach) as narrative vehicle in early nineteenth-century Spain. (2nd January 2021) - Frost, Daniel
ABSTRACT: This article investigates how portrayals of the diligencia (stagecoach) in costumbrista texts, guidebooks and other writings from early nineteenth-century Spain helped characterize the country's transition to modernity. Tracing the growing influence of the stagecoach network in the years before the railroad, the study examines how writers such as Mariano José de Larra and Ramón de Mesonero Romanos employ the diligencia both as a symbol of movement and a literary device well-suited to conveying the quickening pace of life that they observed. Precursor to the tranvía and train, the diligencia occasioned changes in how writers perceived and represented their era. Opening up new means of association, exchange and, ultimately, narration, the diligencia becomes an apt means to comment on the political, social and economic climate of the day.